Assessment of cytotoxicity and toxicity for phosphonium-based deep eutectic solvents - Hayyan, Maan; Hashim, Mohd. Ali; Al-Saadi, Mohammed A.; Hayyan, Adeeb; Alnashef, Inas Muen; Mirghani, Mohamed Elwathig Saeed (Elsevier Inc., 2013)
In this work, the cytotoxicity and toxicity of phosphonium-based deep eutectic solvents (DESs) with three hydrogen bond donors, namely glycerine, ethylene glycol, and triethylene glycol were investigated. The cytotoxicity effect was tested using brine shrimp (Artemia salina). The toxicity was investigated using the two Gram positive bacteria Bacillus subtilis and Staphylococcus aureus, and two Gram negative bacteria Escherichia coli and Pseudomonas aeruginosa. The cytotoxicity of tested DESs was much higher than that of their individual components, indicating their toxicological behavior was different. It was also found that there was toxic effect on the studied bacteria, indicating their potential application as anti-bacterial agents. To the best of our knowledge, this is the first time the cytotoxicity and toxicity of phosphoniumbased DESs were studied.